2023
DOI: 10.1177/03635465221148744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Formal Nonoperative Management Program Combining a Hip Injection With Structured Adjunctive Exercise Rehabilitation in Patients With Symptomatic Femoroacetabular Impingement Syndrome

Abstract: Background: Although the initial treatment recommendations for femoroacetabular impingement syndrome (FAIS) may include nonsurgical therapies such as injections and rehabilitation, many patients undergo isolated injections or a rudimentary exercise regimen. Purpose: To investigate the benefit of an intra-articular hip injection and concomitant structured exercise rehabilitation program in patients with symptomatic FAIS ≥6 months. Study Design: Case series; Level of evidence, 4. Methods: For this study we recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Besides the surgical treatment of femoroacetabular impingement (FAI), conservative therapeutic approaches are also discussed in the current literature. In a more recent publication in 2023, in which injections and physical therapy were combined, Ebert et al were able to achieve a significant improvement in the clinical findings for 32% of their patient cohort in a 2-year follow-up, although no long-term results were described [34]. Despite the therapeutic successes presented in the previously mentioned study using conservative therapy for FAI, a meta-analysis from the year 2020 was already able to demonstrate that surgical treatment is significantly superior to non-operative therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the surgical treatment of femoroacetabular impingement (FAI), conservative therapeutic approaches are also discussed in the current literature. In a more recent publication in 2023, in which injections and physical therapy were combined, Ebert et al were able to achieve a significant improvement in the clinical findings for 32% of their patient cohort in a 2-year follow-up, although no long-term results were described [34]. Despite the therapeutic successes presented in the previously mentioned study using conservative therapy for FAI, a meta-analysis from the year 2020 was already able to demonstrate that surgical treatment is significantly superior to non-operative therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy is a key part of the team providing nonoperative care for individuals with hip joint-related pain 38 . Therapy begins with a compre-hensive examination, which allows the clinician to determine the extent to which a patient's pain problem and movement dysfunction are associated with the structural impairments identified by imaging.…”
Section: Physiatry/nonoperative Managementmentioning
confidence: 99%
“…More recently, a larger case series by Ebert et al examined 44 patients with FAIS and found significant improvement in pain and function after intra-articular corticosteroid injection followed by a structured 12-week rehabilitation program. While these improvements were largely sustained at 24 months, it should be noted that 32% of patients progressed to surgery [51]. It is important to note that these studies include a heterogeneous population which makes it difficult to draw firm conclusions regarding the benefit of corticosteroid injections in FAIS.…”
Section: Intra-articular Hip Injectionsmentioning
confidence: 99%